2007
DOI: 10.1007/s11096-007-9166-3
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy in elderly hospitalised patients in Slovakia

Abstract: Our study confirmed a relatively high prevalence of polypharmacy in Slovak elderly patients. Polypharmacy risk rose especially with the increased prevalence of diseases of advancing age (diabetes mellitus, heart failure, arterial hypertension, dementia and cerebrovascular diseases). The increasing numbers of medications in inpatients indicate the need for the careful re-evaluation of pharmacotherapy during the stay in hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 30 publications
6
32
0
5
Order By: Relevance
“…Some of them include comorbidities, low subjective health, over the counter drug usage [22][23][24] . In our study, we considered the following factors namely age, sex, duration of hospital stay, number of comorbidities and complexity of the procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Some of them include comorbidities, low subjective health, over the counter drug usage [22][23][24] . In our study, we considered the following factors namely age, sex, duration of hospital stay, number of comorbidities and complexity of the procedure.…”
Section: Resultsmentioning
confidence: 99%
“…A survey of community-dwelling elderly showed that more than 90% of those aged 65 years or more used at least one drug weekly and more than 40% took five or more (5). Among hospitalized elderly, the prevalence of polypharmacy ranged from 20% to 60%, reflecting different criteria used to select patients and collect medication data (6)(7)(8). Although polypharmacy has no generally accepted definition, most often it is defined by cut-offs, in terms of the number of medications taken, ranging from two to ten (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…A search in PubMed yielded more than 2000 hits on "polypharmacy" (October 2007). Polypharmacy has been used as an indicator to select patients for research projects, for quality assurance tasks, for example medication reviews, and for describing extensive drug use among patients (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%